Dengue Fever: State-of-the-Art Symptoms and Diagnosis - Kasbe, Tanmay; Pippal, Ravi Singh (International Journal of Computer Sciences and Engineering, 2025)
Fever is the most normal disease in any age group, but it becomes a deadly disease if it has dengue symptoms. Identifying dengue symptoms at an early stage is very difficult because this kind of symptoms is very common in all types of fevers. When fever continues after 3-4 days the symptoms of dengue shown in patients. So far there is no vaccine (According to WHO (World Health Organization) Report in April 2015 First Dengue fever vaccine introduced. We have mention about in this paper) or particular medicine available in market to prevent from the dengue. In today era around 40% population of the world is at risk of dengue fever. Since 1950s, this disease cause several death on globe and unfortunately there is no proper preventive method developed yet. From the long period of time some senior doctors working on categorized dengue fever because symptoms of dengue fever are different for different patients. In this paper we have to provide all cause, symptoms & diagnosis methods.